Can motor competence be influenced by the type of training interventions preschool children are exposed to? A randomized experimental study comparing sports games and psychomotricity activities - Guo, Xiaodan; Li, Chuangtao; Zhang, Zhaoxiang; Silva, Ana Filipa; Clemente, Filipe Manuel (Frontiers in Psychology, 2024)
IntroductionThis study aimed to compare the effects of structured sports games (SG) and psychomotricity activities (PCM) on the locomotor, stability, and manipulative motor competencies of preschool children.MethodsA randomized controlled trial was conducted over an 8-week period, involving two experimental groups (SG, n = 30 and PCM, n = 30) and one control group (CG, n = 28), with participants attending two intervention sessions per week. A total of 88 5-year-old children participated in the experiment (boys n = 48; girls n = 40). They were evaluated three times (at baseline, after 4 weeks, and after 8 weeks) using the Motor Competence Assessment test to measure their locomotor, stability, and manipulative motor competencies.ResultsThe scores were standardized to percentiles based on sex and age. However, significant differences were observed between groups post-intervention in the locomotor domain (p = 0.003; ηp2 = 0.128), with the SG showing significantly higher values compared to the CG (mean difference: 17.0%; p = 0.021; d = 0.783), and PCM (mean difference: 19.8%; p = 0.005; d = 0.947). Additionally, significant differences were found between groups post-intervention in the manipulative domain (p = 0.001; ηp2 = 0.142), with the SG showing significantly higher values compared to the CG (mean difference: 19.3%; p = 0.009; d = 0.845) and PCM (mean difference: 21.4%; p = 0.003; d = 0.998).DiscussionOur study highlights the significant benefits of increased practice in developing motor competence, particularly in children’s locomotor and manipulative skills. Additionally, at this age, fun, competition, and social interaction seem to play a crucial role, as the SG group demonstrated greater improvements compared to the PCM group.